Molecular mechanisms of tigecycline-resistance among Enterobacterales - Korczak, Lukasz; Majewski, Piotr; Iwaniuk, Dominika; Sacha, Pawel; Matulewicz, Mariola; Wieczorek, Piotr; Majewska, Paulina; Wieczorek, Anna; Radziwon, Piotr; Tryniszewska, Elzbieta (Frontiers in Cellular and Infection Microbiology, 2024)
The global emergence of antimicrobial resistance to multiple antibiotics has recently become a significant concern. Gram-negative bacteria, known for their ability to acquire mobile genetic elements such as plasmids, represent one of the most hazardous microorganisms. This phenomenon poses a serious threat to public health. Notably, the significance of tigecycline, a member of the antibiotic group glycylcyclines and derivative of tetracyclines has increased. Tigecycline is one of the last-resort antimicrobial drugs used to treat complicated infections caused by multidrug-resistant (MDR) bacteria, extensively drug-resistant (XDR) bacteria or even pan-drug-resistant (PDR) bacteria. The primary mechanisms of tigecycline resistance include efflux pumps’ overexpression, tet genes and outer membrane porins. Efflux pumps are crucial in conferring multi-drug resistance by expelling antibiotics (such as tigecycline by direct expelling) and decreasing their concentration to sub-toxic levels. This review discusses the problem of tigecycline resistance, and provides important information for understanding the existing molecular mechanisms of tigecycline resistance in Enterobacterales. The emergence and spread of pathogens resistant to last-resort therapeutic options stands as a major global healthcare concern, especially when microorganisms are already resistant to carbapenems and/or colistin.